CROSSFIT AS A NEW CHAPTER IN THE CADETS' PHYSICAL TRAINING SYSTEM - Mirzakulov Akrоm Gafurzhanovich (PEDAGOGS, 2024)
Abstract: Crossfit can be described as a training program consisting of “constantly varying high-intensity functional exercises”. The purpose of the technique is formulated as the physical development of a person in such areas as endurance, strength, flexibility, speed, coordination, accuracy, as well as improving the performance of the cardiovascular and respiratory systems, speed of adaptation to changing loads, etc. The Crossfit training program is suitable for any kind of sport (for people of different training levels).